Game Perspective-Taking Effects on Players' Behavioral Intention, Attitudes, Subjective Norms, and Self-Efficacy to Help Immigrants: The Case of "Papers, Please" - Peña, Jorge; Hernández Pérez, Juan Francisco; Khan, Subuhi; Cano Gómez, Ángel Pablo (Cyberpsychology, behavior and social networking, 2018)
This study expands on game character perspective-taking effects on political opinions while controlling for players' social dominance orientation or inclination for inequality among social groups. Random assignment to play a game as an immigration inspector decreased intention, subjective norms, and self-efficacy to help immigrants relative to baseline scores. The scores of participants randomly assigned to play a game similar in style but instead featuring the role of a newspaper editor remained unchanged. Within-subjects effects implied that baseline reductions in intention, subjective norms, and self-efficacy to help immigrants were solely attributed to playing games as game immigration inspectors. The study provides initial evidence that taking on the perspective of game characters can influence players' opinions about political issues, such as immigration.